Morphological and anatomical adaptations to dry, shady environments in Adiantum reniforme var. sinense (Pteridaceae) - Di Wu; Linbao Li; Xiaobo Ma; Guiyun Huang; Chaodong Yang (PeerJ, 2020)
The natural distribution of the rare perennial fern Adiantum reniforme var. sinense (Pteridaceae), which is endemic to shady cliff environments, is limited to small areas of Wanzhou County, Chongqing, China. In this study, we used brightfield and epifluorescence microscopy to investigate the anatomical structures and histochemical features that may allow this species to thrive in shady, dry cliff environments. The A. reniforme var. sinense sporophyte had a primary structure and a dictyostele. The plants of this species had an endodermis, sclerenchyma layers and hypodermal sterome, reflecting an adaption to dry cliff environments. Blades had a thin cuticle and isolateral mesophyll, suggesting a tolerance of shady environments. These characteristics are similar to many sciophyte ferns such as Lygodium japonicum and Pteris multifida. Thus, the morphological and anatomical characteristics of A. reniforme var. sinense identified in this study are consistent with adaptations to shady, dry cliff environments.